Analisis Efektivitas Manajemen Keuangan pada BPKAD Provinsi Sumatera Utara - Djauky Ridho Amwa Amwa; Nurbaiti Nurbaiti (VISA: Journal of Vision and Ideas, 2023)
Medan City is the largest economic contributor in North Sumatra. Based on data from the Central Statistics Agency (BPS), the city's gross regional domestic product (GRDP) at current prices (ADHB) is IDR 242.2 trillion in 2020. This value is equivalent to 30% of North Sumatra's total GRDP of IDR 811.3 trillion . This study uses a qualitative research approach. By way of terminology for Baydan and Taylor, a qualitative approach is a research method that creates descriptive information in the form of recorded words or utterances. The results of the study show that what was carried out at the Financial Institutions and Regional Assets in North Sumatra Province regarding Financial Performance of the Regional Expenditure Budget According to the data analysis that has been carried out, it can be concluded that the Regional Financial Independence Ratio is still below regional financial standards. Keywords: Efficiency, Effectiveness, BPKAD